ANALYSIS OF THE RESULTS OF REFORMING THE HEALTH CARE SYSTEM BASED ON THE REPORTING DOCUMENTATION OF THE NATIONAL HEALTH SERVICE - SHYSHKA Іhor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article summarizes the concept and main stages of reforming the health care sector of Ukraine and the main tasks of the reform. The report data of the National Health Service of Ukraine (NHSU) and digests of changes in the health care system for the period 2018-2022 were analyzed in the following directions: periodization and main tasks of the reform; the dynamics of concluding contracts between medical institutions and the National Health Service; the dynamics of the number of signed declarations for the provision of primary medical care; the dynamics of payments to medical institutions of various forms of ownership that have concluded an agreement with the National Health Service; the amount of financing of the main types of medical care in accordance with the Program of Medical Guarantees; the dynamics of the main performance indicators of the drug reimbursement program; development of electronic tools for the doctor`s work. Comparing the evaluations of different stakeholders makes it possible to increase the objectivity of evaluating the results of the implementation of certain changes. It was determined that the results of the implementation of the reform are exceptionally positive according to the estimates of the NHSU. Among them: the annual increase in the number of concluded contracts between medical institutions and NHSU; an increase in the share of private institutions and doctors-individuals working at the primary level of medical care; annual increase in the number of signed declarations for the provision of PMC; growth in the amount of payments to medical institutions of all forms of ownership; expansion of the list of medical services in the guaranteed package; an increase in the number of patients who received drugs under the reimbursement program; preservation of positive dynamics of financing volumes for all types of medical care despite the war; annual increase in the electronic tools of the doctor`s work.